Some Aspects Of The Biology And Population Dynamics Of Goatfish, Upeneus Spp. In Terengganu Waters, Peninsular Malaysia - Rahardjo, Priyanto (1997)

(untitled)
Two species of goatfish or Biji nangka, Upeneus sulphureus and U . bensasi play a significant role in the demersal trawl fishery in the Terengganu waters. Estimation of their population parameters, i.e., growth, reproductive behaviour, mortality rate, and assessment of the effect of changes in exploitation pattern were carried out, and alternative management measures for the fishery were examined.Growth parameters were estimated based on modal progression analysis of length frequency distributions. Data on sexual maturity and seasonal changes in the gonadosomatic index were used to elucidate the reproductive biology of the two species .Length-based catch curves were used to estimate total mortality rate ( Z ) while empirical and indirect methods were used to estimate natural mortality rate (M). Relative yield per recruit as a function of exploitation rate E , ( E= F / ( F+M) , ratio of natural mortality M and Von Bertalanffy growth parameter K , ( M/ K ) , and size at first capture (Lc ) , was used to analyze the effects of variability in the controlled variables E and/or Lc.Estimates of the growth parameters derived from eight different methods were K = 0.80 to 1 .4 5 , Loo = 218.08 to 232.00 mm for U. sulphureus and K = 0.90 to 1.38 , Loo 22 8.00 to 243 .31 mm for U. bensasi. Estimates of total mortality derived from three different methods employed varied ( Z = 3.30 to 5.93 for U. sulphureus and Z = 2 . 65 to 5.57 for U . bensasi) so considerably that the validity of the methods was questioned. Further validation of the results derived from the length-based method is necessary. Estimates of natural mortality derived from three different methods for upeneus sulphureus (M = 1.01 to 2 .53 ) were less varied than for Upeneus bensasi (M = 1 .18 to 2.84 ). Finally , consideration of management policy using an EO .1 criterion ( analogous to F0.I ) showed that the current level of exploitation rate ( E =0.63 ) for U. sulphureus exceeded the estimate of the E 0. I level ( E =0.5 7 ) , while for U. bensasi ( E=0 . 51) it was below the E0.1 level ( E=0.6 7 ).